Propuesta del diseño de productos turísticos sustentables con base en las TIC para el fomento del turismo en la ruta turística pueblo Mágico, Roldanillo, Valle del Cauca (2021)
This document presents the results of the research that aimed to elaborate the proposal for sustainable tourism products based on ICT for the promotion of tourism in the Pueblo Mágico tourist route, Roldanillo, Valle del Cauca. For this purpose, three specific objectives were developed. Initially, the Magic Town tourist route, Roldanillo, was characterized, starting with a description of the municipality, its tourist inventory, products and the agents belonging to the route. Then, a documentary review was carried out on the theoretical and conceptual bases for the design of sustainable tourism products based on ICT, where emphasis was placed on the characteristics of tourism products and the way in which information technologies can contribute to its development.